A Novel Aqueous Micellar Two-Phase System Composed of Surfactant and Sorbitol for Purification of Pectinase Enzyme from Psidium guajava and Recycling Phase Components. (10th February 2015) - Amid, Mehrnoush; Murshid, Fara Syazana; Manap, Mohd Yazid; Hussin, Muhaini
Abstract : A novel aqueous two-phase system composed of a surfactant and sorbitol was employed for the first time to purify pectinase from Psidium guajava . The influences of different parameters, including the type and concentration of the surfactant and the concentration and composition of the surfactant/sorbitol ratio, on the partitioning behavior and recovery of pectinase were investigated. Moreover, the effects of system pH and the crude load on purification fold and the yield of purified pectinase were studied. The experimental results indicated that the pectinase was partitioned into surfactant-rich top phase, and the impurities were partitioned into the sorbitol-rich bottom phase with the novel method involving an ATPS composed of 26% (w/w) Triton X-100 and 23% (w/w) sorbitol at 54.2% of the TLL crude load of 20% (w/w) at pH 6.0. The enzyme was successfully recovered by this method with a high purification factor of 15.2 and a yield of 98.3%, whereas the phase components were also recovered and recycled at rates above 96%. This study demonstrated that this novel ATPS method can be used as an efficient and economical alternative to the traditional ATPS for the purification and recovery of the valuable enzyme.